2016
DOI: 10.1128/jvi.00283-16
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Non-Replication-Competent Cytomegalovirus Capsid Mutant Vaccine Strategy Is Effective in Reducing Congenital Infection

Abstract: Congenital cytomegalovirus (CMV) infection is a leading cause of mental retardation and deafness in newborns. The guinea pig is the only small animal model for congenital CMV infection. A novel CMV vaccine was investigated as an intervention strategy against congenital guinea pig cytomegalovirus (GPCMV) infection. In this disabled infectious single-cycle (DISC) vaccine strategy, a GPCMV mutant virus was used that lacked the ability to express an essential capsid gene (the UL85 homolog GP85) except when grown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(96 citation statements)
references
References 94 publications
(158 reference statements)
6
89
0
1
Order By: Relevance
“…Another option to increase safety is the application of replication- and spread-deficient vaccine strains. Studies in the mouse model revealed that such strains preserve the ability to stimulate CMV-specific T cell immunity [82, 83], and in a guinea pig model of congenital CMV infection partial protection of pups was observed following immunization with a non-infectious guinea pig CMV BAC DNA vaccine [84] or with a non-replication-competent virus [85]. We have recently pioneered the development of conditional-replicating CMV strains [86], and this technique has already successfully been used to generate a conditionally replicating HCMV vaccine candidate, which is currently in phase 1 testing (ClinicalTrials.gov number, NCT01986010).…”
Section: Discussionmentioning
confidence: 99%
“…Another option to increase safety is the application of replication- and spread-deficient vaccine strains. Studies in the mouse model revealed that such strains preserve the ability to stimulate CMV-specific T cell immunity [82, 83], and in a guinea pig model of congenital CMV infection partial protection of pups was observed following immunization with a non-infectious guinea pig CMV BAC DNA vaccine [84] or with a non-replication-competent virus [85]. We have recently pioneered the development of conditional-replicating CMV strains [86], and this technique has already successfully been used to generate a conditionally replicating HCMV vaccine candidate, which is currently in phase 1 testing (ClinicalTrials.gov number, NCT01986010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clear evidence that would suggest the production of potent neutralizing antibodies against the GPCMV PC (similar to the previously isolated human antibodies that predominantly target conformational epitopes of the UL128/130/131A subunits of the HCMV PC) was absent. Even more importantly, the protective studies were compared to historical controls that were based on responses engendered against a PC-negative "first generation" DISC vaccine [62] using a different dose regimen. The authors noted that, although both two-and three-dose regimens were examined for immunogenicity with the DISC vaccine, protection studies for the first-generation vaccine were completed using only those dams immunized with the suboptimal, two-dose vaccine regimen [62].…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that, although potently-neutralizing CMV-specific antibodies can effectively reduce viral population size and prevent congenital transmission [9], preexisting HIG had limited impact on the genetic makeup of the maternal RhCMV populations or transmitted variants. These findings are interesting given the growing evidence that preexisting HCMV-specific antibodies can reduce the incidence and severity of congenital HCMV [9,3840], perhaps suggesting a model wherein congenital virus transmission is dependent upon the overall quantity of maternal systemically-circulating virus rather than antibody selection of specific variants at the maternal-fetal interface. Further studies, ideally starting with an inoculum containing higher levels of viral diversity, may be required to provide a deeper understanding of the extent of antibody-mediated immune-pressure on CMV populations, as well as the effect of antibodies on viral transmission dynamics across the placenta.…”
Section: Discussionmentioning
confidence: 99%